Global brands the evolution of multinationals in alcoholic beverages - "Lopes, Teresa Da Silva" (New York, 2007)
In a world focused on science and new technology, brands help to explain why several of the world's multinational corporations have little to do with either. Rather they are old firms with little critical investment in patents or copyrights. For these firms, the critical intellectual property is trademarks. Global Brands, first published in 2007, explains how the world's largest multinationals in alcoholic beverages achieved global leadership; considers the predominant corporate governance structures for such firms; and looks at why these firms form alliances with direct competitors. Brands also determine the waves of mergers and acquisitions in the beverage industry. Global Brands contrasts with existing studies by providing a new dimension to the literature on the growth of multinationals through the focus on brands, using an institutional and evolutionary approach based on original and published sources about the industry and the firms.
Keywords: Alcoholic beverage industry